Business responsibility for sustainable development - Peter Utting (United Nations Research Institute for Social Development (UNRISD), 2000)
Development agencies and actors concerned with promoting sustainable development have been joined in recent years by another player - big business. Increasing adherence on the part of senior managers to concepts like corporate citizenship or corporate social responsibility suggests that this sector of business is beginning to recast its relationship with both the environment and its multiple stakeholders. This evolving situation stands in sharp contrast to the scenario of the past when big business was seen to be insensitive to the needs of certain stakeholders and responsible for much of the environmental degradation of the planet. This paper assesses the reality behind the claims of some sectors of business that an increasing number of large firms are adopting policies and practices conducive to the promotion of sustainable development, particularly in developing countries. After describing various institutional developments that have occurred in the 1990s and that appear to be promoting corporate social and environmental responsibility, the paper assesses the current state of play, highlighting in particular the incipient and piecemeal nature of change. It goes on to examine whether there are forces or an enabling environment in place that might permit a scaling up of initiatives associated with corporate responsibility. Some of the more powerful forces that drive corporate responsibility are identified. The question of why some sectors of business are changing reveals an answer that has less to do with a new-found ethical concern among corporate executives for the environmental and social condition of the planet, than with economic, political and structural factors. These include so-called "win-win" opportunities, the possibility of enhancing competitive advantage, "reputation management", pressure group and consumer politics, regulation or the threat of regulation, and changes in the way production and marketing are being organized globally. While such "drivers" may encourage corporations to be more responsive to environmental and social concerns, it is argued that the process of change is likely to remain fairly fragmented, spread unevenly in terms of companies, countries and sectors, and, from the perspective of sustainable development, fraught with contradictions. What amounts to a fairly minimalist and uneven agenda is not simply a reflection of the fact that the process of change is of recent origin; it also derives from the way in which companies choose to respond to the economic, political and structural drivers of change - responses that often involve imagery, public relations and relatively minor adjustments in management systems and practices, as opposed to significant changes in the social and environmental impact of a company's activities. The final section of the paper reflects on how trends associated with corporate environmental and social responsibility might be both scaled up and "deepened", so that business can make a more meaningful contribution to sustainable development. It begins by considering whether the dominant approach that is currently in vogue centred on the promotion of "voluntary initiatives" and "partnerships" is likely to be effective. While there are important benefits that can derive from such institutional arrangements, there may also be a considerable downside that is often overlooked. The success of many voluntary initiatives requires a certain institutional setting - for example, basic laws related to disclosure and freedom of information, watchdog institutions and strong civil society movements. Such conditions may be weak or absent in many countries. Furthermore, certain initiatives, such as codes of conduct and certification systems, have often been designed by Northern actors, be they governments, NGOs or corporate interests. Southern governments and NGOs are often marginalized in the decision-making processes that affect them. Too often, voluntary initiatives are held up as substitutes for government regulation when in fact various forms of legislation and state sanctions are often what motivated such initiatives in the first place and are crucial for their success. Despite the obvious appeal of the pragmatic and co-operative features of "partnerships", involving, for example, business and United Nations agencies or NGOs, serious questions are raised about their impact. Of particular concern are issues related to the weak criteria often used by United Nations and other organizations to select corporate partners, the way in which more critical voices are silenced as NGOs and United Nations agencies get closer to business, and the problem of "institutional capture" as business comes to exercise influence over decision-making processes associated with the public sphere. Perhaps the most significant concern with some forms of voluntary initiatives and partnerships is that they may serve to weaken key drivers of corporate responsibility - namely government regulation, collective bargaining and certain forms of civil society activism. If one examines the history of corporate environmental and social responsibility, and some of the major reforms of corporate policies and practices, one or a combination of these factors has been crucial. The paper ends with a call for "rethinking regulation and partnerships". There is potentially an important role for certain forms of "co-regulation". These may involve, for example, so-called "negotiated agreements" between government and business, and "civil regulation", where NGOs, consumers and trade unions have considerable influence in determining the standards and norms shaping business relations with society and the environment. Key to the success of co-regulation are not only the "softed" features of dialogue and compromise, but also the "hard" ones of government sanctions; laws related to disclosure and freedom of information, freedom of association and collective bargaining; and various forms of civil society protest. To avoid the ongoing proliferation of weak codes of conduct and certification and reporting systems, it is important that there be some degree of harmonization and adherence to higher standards. This implies a greater role for international codes and frameworks, which use as benchmarks internationally agreed standards contained or implied in such documents as Agenda 21 and ILO and human rights conventions. There should also be a greater role for "independent verification" of codes of conduct, environmental management systems and UN-business partnerships. Greater attention needs to be paid, however, to the status or legitimacy of the verifiers. Rethinking partnerships involves not only addressing the concerns raised above, but also recognizing the need to build a stronger civil society movement for change by strengthening links between environmentalists, consumer groups, social-interest NGOs and trade unions.
Keywords: 330